2015
DOI: 10.53671/pturj.v3i1.35
|View full text |Cite
|
Sign up to set email alerts
|

Sensing tomato’s pathogen using Visible/Near infrared (VIS/NIR) spectroscopy and multivariate data analysis (MVDA)

Abstract: Quality of agricultural products is a very important issue for consumers as well as for farmers in relation to price, health and flavour. One of the factors that determine the quality is the absence of pathogens that can cause diseases for products and also for consumers. An advanced method to sense pathogens and their antagonists is the use of Visible/Near Infrared (VIS/NIR) spectroscopy. In this paper, the VIS/NIR spectroscopy, with the help of two techniques of multivariate data analysis (MVDA); namely prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…During spectral analysis, this method showed a spectral shift due to the leaking from cabbage cells and the growth of bacteria ( 82 ). This shifting behavior was treated using the SG-derivative method ( 82 ), followed by tomato pathogen analysis ( 83 ). Spectral analysis revealed that the shredded samples had better separation between inoculation times than the ground samples ( 82 ), which makes the former the method of choice for analysis.…”
Section: Applications Of Spectroscopic Techniquesmentioning
confidence: 99%
See 3 more Smart Citations
“…During spectral analysis, this method showed a spectral shift due to the leaking from cabbage cells and the growth of bacteria ( 82 ). This shifting behavior was treated using the SG-derivative method ( 82 ), followed by tomato pathogen analysis ( 83 ). Spectral analysis revealed that the shredded samples had better separation between inoculation times than the ground samples ( 82 ), which makes the former the method of choice for analysis.…”
Section: Applications Of Spectroscopic Techniquesmentioning
confidence: 99%
“…A study on tomato pathogen analysis achieved a classification accuracy rate of 99.3% on the first and second day using PCA followed by an SVM classifier ( 83 ). Although higher classification rates were achieved as the mixing of samples began, the SVM classification could not handle multiple factors affecting the same.…”
Section: Applications Of Spectroscopic Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, research conducted by CIHEAM of Bari showed the application of RS in the monitoring of two quarantine pathogens in the Apulia region (Italy): Citrus tristeza virus (CTV) and Xylella fastidiosa [4]. Visible/near-infrared (VIS/NIR) and thermal (TIR) imaging techniques have been applied for detecting the stress condition of plants infected by pathogens, such as fungi [5,6], bacteria [7] and viruses, e.g., tobacco mosaic virus [8], grape leaf roll-associated virus-3 [9] or sugarcane yellow leaf virus [10].…”
Section: Introductionmentioning
confidence: 99%